2022
DOI: 10.1101/2022.10.08.511447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skipper analysis of RNA-protein interactions highlights depletion of genetic variation in translation factor binding sites

Abstract: Technology for crosslinking and immunoprecipitation followed by sequencing (CLIP-seq) has identified the transcriptomic targets of hundreds of RNA-binding proteins in cells. To increase the power of existing and future CLIP-seq datasets, we introduce Skipper, an end-to-end workflow that converts unprocessed reads into annotated binding sites using an improved statistical framework. Compared to existing methods, Skipper on average calls 3.1-4.2 times more transcriptomic binding sites and sometimes >10 times … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 84 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…DDX42-dTAG HCT-116 cells were treated with WX-02-23 (5 µM), WX-02-43 (5 µM), or Pladienolide B (100 nM) for 3 h. Data are average values from two independent experiments. eCLIP enriched windows (FDR<0.2) were called and annotated using the Skipper analysis pipeline (Boyle et al ., 2022) and are depicted as percent binding relative to coding sequence (CDS). Proximal denotes within 500 bases and adjacent denotes within 100 bases from the annotated splice site (SS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DDX42-dTAG HCT-116 cells were treated with WX-02-23 (5 µM), WX-02-43 (5 µM), or Pladienolide B (100 nM) for 3 h. Data are average values from two independent experiments. eCLIP enriched windows (FDR<0.2) were called and annotated using the Skipper analysis pipeline (Boyle et al ., 2022) and are depicted as percent binding relative to coding sequence (CDS). Proximal denotes within 500 bases and adjacent denotes within 100 bases from the annotated splice site (SS).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis more directly, we evaluated DDX42-mRNA interactions by eCLIP-seq (enhanced crosslinking and immunoprecipitation followed by sequencing) (Van Nostrand et al, 2016) using the hemagluttinin (HA) epitope tag component of the dTAG fusion. These eCLIP-seq experiments revealed that, in untreated cells, DDX42 mainly bound to the coding region of (pre-)mRNAs, but, following exposure of cells to SF3B1 ligands WX-02-23 or pladienolide B, the DDX42-RNA interaction preferences strongly shifted towards regions within or near splice sites (Figure 7F and G and Dataset S2) (Boyle et al, 2022;Van Nostrand et al, 2020). Our results, taken together, thus suggest that DDX42 dynamically binds SF3B1 as part of an A-like spliceosome complex that is in close contact with (pre-)mRNAs and splice sites to facilitate branch point selection.…”
Section: Ddx42 Facilitates Spliceosome Branch Point Selectionmentioning
confidence: 93%
See 1 more Smart Citation